Influência da contaminação por Trypanosoma cruzi (Kinetoplastida: Trypanosomatidae) na espermatogênese de Triatomíneos (Hemiptera: Reduviidae) - Pereira, Nathália Paiva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The insects of the Triatominae, also known as barbers, have a great importance in human parasitology, as are vectors of Trypanosoma cruzi protozoan that causes Chagas disease. In addition to medical and health importance, these insects stand out in cytogenetics, due to peculiar characteristics as holocentric chromosomes, and an unusual meiosis, in which the autosomes segregate regularly, while the sex chromosomes present the first equational division and the second reductive. In addition, several studies are conducted to identify the effects of physiological stress in the body of these insects. However, there are no studies evaluating the influence of contamination of insects Trypanosoma cruzi in the reproduction of these individuals. For this, we analyzed the cytogenetic characteristics during spermatogenesis three triatomine species: Triatoma brasiliensis, Rhodnius neglectus and Panstrongylus megistus, which were infected in the laboratory with T. cruzi. Later blades were made with the testicles of these insects and stained by conventional cytogenetic technique and performed cell counts to quantitatively determine these cells in the testes. It was possible to observe an increase in cell size of polyploid nuclei, nutritional cells present in the seminiferous tubules and all cells during spermatogenesis, plus a disruption in nuclear and nucleolar during cell division. Furthermore, there was a decrease in cell quantities given infected individuals, an increase in the number of polyploid cells and nuclei in interphase, and a decrease in cell division. These changes may be due to physiological stress that infection with T. cruzi caused to the body of these insects. In addition, cells in interphase and early chromosome condensation had higher heteropycnotic corpuscles in contaminated than in those who were free of protozoan that causes Chagas disease showing that the physiological stress organisms may be the main reason for this change in...

Os insetos da subfamília Triatominae, também conhecidos como barbeiros, possuem uma grande importância na parasitologia humana, pois são vetores do Trypanosoma cruzi, protozoário causador da doença de Chagas. Além da importância médicosanitária, esses insetos destacam-se na citogenética, por apresentarem características peculiares como cromossomos holocêntricos, e uma meiose incomum, na qual os autossomos segregam-se de maneira regular, enquanto que os cromossomos sexuais apresentam a primeira divisão equacional e a segunda reducional. Além disso, diversos estudos são realizados para identificar os efeitos do estresse fisiológico no organismo desses insetos. Entretanto, não há estudos avaliando a influência da contaminação de triatomíneos pelo Trypanosoma cruzi na reprodução desses indivíduos. Para isso foram analisadas as características citogenéticas durante a espermatogênese de três espécies de triatomíneos: Triatoma brasiliensis, Rhodnius neglectus e Panstrongylus megistus, que foram infectadas em laboratório, pelo T. cruzi. Posteriormente, foram confeccionadas lâminas com os testículos desses insetos e coradas por técnica citogenéticas convencionais e, também, realizada contagem celular para verificar quantitativamente as células presentes nos testículos. Foi possível observar um aumento no tamanho celular dos núcleos poliploides, células nutritivas presentes nos túbulos seminíferos, e de todas as células durante a espermatogênese, além de uma desorganização no material nuclear e nucleolar durante a divisão celular. Além disso, foi observado um decréscimo nas quantidades celulares de indivíduos contaminados, com aumento no número de núcleos poliploides e células em intérfase, e uma diminuição de células em divisão. Essas alterações podem ter ocorrido devido ao estresse fisiológico que a infecção por T.cruzi causou ao organismo desses...
Keywords: Biologia; Citogenetica; Barbeiro; Trypanosoma cruzi; Stress; Espermatogenese